â€œListening is Hardâ€: ADDIE Model on the Development of English Listening Worksheets - Furwana, Dewi; Syam, Andi Tenrisanna (Language Circle: Journal of Language and Literature, 2021)
The authors’ pre-observation showed that when students learn listening skills, the students faced some difficulties. The students found difficulty expressing their ideas because they found many complex vocabularies, the audio text uses advanced grammar, and the native speaker speaks too fast. Therefore, to solve those students’ problems, the authors proposed to develop the appropriate listening worksheet for the English education study program of IAIN Palopo. Then, the authors applied Research and Development method and used the ADDIE model. 18 students of the English education study program IAIN Palopo were involved as the research subject. The research instruments used were observation and questionnaire. From observing, analysing students’ needs, developing the materials, evaluating expert judgments, conducting try-out materials, revising the product, the final product of this study is listening worksheets stored in a compact disc. The worksheets consist of a course grid, learning objective, language note, pre-activity, whilst-activity and post-activity. The authors expect that this worksheet will be useful for EFL teachers whose students' listening skills are still below the expected level of competence.